Preparation of a hydrophobic cerium oxide nanoparticle coating with polymer binder via a facile solution route. Issue 8 (1st June 2020) - Yasmeen, Sumaira; Khan, Mohammad Rizwan; Park, Kiho; Cho, Yunshik; Choi, Jang Wook; Moon, Hyoung-Seok; Lee, Han-Bo-Ram
Abstract: In this work, cerium oxide (CeO2 ) nanoparticles (NPs) were synthesized using a facile, low temperature solution process and coated using spin coating and spray coating approaches, for the fabrication of a hydrophobic surface coating. Silicon wafer (Si) substrates coated with CeO2 NPs exhibited excellent hydrophobic behavior, but poor adhesion of the NPs to the substrate was observed - likely due to the low surface polarity of CeO2 NPs. Polyacrylic acid (PAA) was introduced as an adhesion promoter to improve NP surface characteristics and obtain an adherent and cohesive coating. Slight polarity tuning and binder inclusion significantly enhanced the binding capability of the NPs as determined by peel-off measurements. The superior mechanical properties of NP coatings were attributed to the incorporation of PAA in the polymeric network. It improves inter-particle and particle-substrate secondary interactions, ultimately aiding NP cohesion and adhesion when deposited onto the Si substrate. The adhesive and hydrophobic properties of CeO2 NP coatings were maintained upon exposure to high temperatures, and the coatings are transparent as well, making them suitable for various applications, such as cookware, glass coating and technology components. Graphical abstract: Image 1